Research on Innovation of Diffusion Mechanism of Intangible Cultural Heritage in the Context of Meta-Universe - Yang, Ruikai; Yuan, Chengxi; Liu, Huifen (International Journal of Social Sciences and Public Administration, 2025)
In the context of the current state actively promoting the protection and inheritance of intangible cultural heritage, it is of great importance to explore the impact of emerging digital platforms on the dissemination of intangible cultural heritage. With the rapid development of digital economy, traditional intangible cultural heritage is faced with many challenges such as limited transmission scope and single transmission mode. Through the case analysis of China's intangible cultural heritage, this paper explores the application strategy of the meta-universe. Through digital reconstruction, digital twin, VR, AR and regional chain and other technologies, intangible cultural transmission is not limited by time and space for effective communication. Combined with the subjective factors faced, finally explore the innovation path of communication mechanism.